(3GdfbhO h GdHfhc (B/s - (3GdYUGQ, QTGOs; (3GdMdHj, QjGV s ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3OQGSI GdfbhO h GdfXe GdfbOjI h GdGUOGQ GdfbOj , Shb GdfbhO eY GdJWQb Gdi GfTCI h JWhQG deUGQa GdJLGQjI , , GdSjGSGJ GdfbOjI , GdJVNe h GfhGYg h BKGQg(B.s
(3eQGLY U(B.172s
Keywords: (3GdHfhcs; (3GdSjGSI GdfbOjIs; (3GdfbhOs